Association between Types of Diabetes and Amniotic Fluid Disorders during Pregnancy: A Cohort Study in South Korea - Kang, Soo Hyun; Park, Minah; Moon, Jong Youn; Kim, Suk Young (HIRA Research, 4(2), 2024)
Background: As the prevalence of maternal diabetes (both pre-pregnancy- and pregnancy-related) is rising, studies on amniotic fluid disorders related to maternal diabetes are necessary. This study aimed to examine whether the type of diabetes affects the risk of amniotic fluid disorders during pregnancy. Methods: Data from the South Korean NHIS-NHID (National Health Insurance Service National Information Database) from 2010 to 2015 were used in this study. Participants were classified into the following five groups: type 1 diabetes, type 2 diabetes, other types of diabetes, gestational diabetes, and without diabetes. Amniotic fluid disorders included polyhydramnios and oligohydremia. Logistic regression analysis was performed to examine the significance of the association between the types of diabetes and amniotic fluid disorders. Results: A total of 1,526,365 women gave birth between 2011 and 2015. Those with gestational diabetes, type 1 diabetes, and type 2 diabetes were more likely to develop amniotic fluid disorders compared to those with no diabetic history (gestational diabetes: odds ratio [OR] 1.19, 95% confidence interval [CI] 1.16–1.21; type 1 diabetes: OR 1.30, 95% CI 1.12–1.51; type 2 diabetes: OR 1.26, 95% CI 1.21- 1.31). Furthermore, there was an increased probability of developing type 1 diabetes among pregnant women younger than 20 years of age (OR 6.62, 95% CI 2.11–20.83). Conclusion: Our findings suggest that regardless of the type of diabetes, those with type 1 diabetes, type 2 diabetes, or gestational diabetes were more likely to develop amniotic fluid disorders. Therefore, monitoring diabetes in pregnant women is necessary as it is vital for the health of the fetus and the pregnant woman. KCI Citation Count: 0